2014
DOI: 10.1016/j.freeradbiomed.2014.05.024
|View full text |Cite
|
Sign up to set email alerts
|

β1-Adrenergic blockers exert antioxidant effects, reduce matrix metalloproteinase activity, and improve renovascular hypertension-induced cardiac hypertrophy

Abstract: Hypertension induces left-ventricular hypertrophy (LVH) by mechanisms involving oxidative stress and unbalanced cardiac matrix metalloproteinase (MMP) activity. We hypothesized that β1-adrenergic receptor blockers with antioxidant properties (nebivolol) could reverse hypertension-induced LVH more effectively than conventional β1-blockers (metoprolol) when used at doses that exert similar antihypertensive effects. Two-kidney one-clip (2K1C) hypertension was induced in male Wistar rats. Six weeks after surgery, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 47 publications
2
28
0
Order By: Relevance
“…The effect of nebivolol on MMP‐2 and ‐9 levels in renal IRI model has not been reported so far. However, in an experimental two kidney one clamp (2K1C) renovascular hypertension model, nebivolol as a nitric oxide (NO) donator, was proven to reduce MMP‐2 activity induced by reactive oxygen species (ROS) . In support of this evidence, another anti‐oxidant drug, tempol, was shown to decrease both TGF‐β and MMP‐2 upregulation caused by oxidative stress in a 2K1C hypertensive rats and ameliorated cardiac hypertensive changes .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The effect of nebivolol on MMP‐2 and ‐9 levels in renal IRI model has not been reported so far. However, in an experimental two kidney one clamp (2K1C) renovascular hypertension model, nebivolol as a nitric oxide (NO) donator, was proven to reduce MMP‐2 activity induced by reactive oxygen species (ROS) . In support of this evidence, another anti‐oxidant drug, tempol, was shown to decrease both TGF‐β and MMP‐2 upregulation caused by oxidative stress in a 2K1C hypertensive rats and ameliorated cardiac hypertensive changes .…”
Section: Discussionmentioning
confidence: 97%
“…Inhibition of matrix metalloproteinases has been shown to reduce IRI in renal murine models . Treatment with β‐adrenergic blockers with anti‐oxidant properties attenuated hypertension‐induced increases in cardiac MMP‐2 levels, and inhibited MMP activity upregulation in two‐kidney one‐clamp induced hypertension in rats . Nebivolol, a third generation β 1 ‐adrenergic receptor blocker with the capability to release NO from endothelium, has been shown to attenuate detrimental effects of pro‐oxidant and inflammatory mechanisms involving tissue growth factor‐β (TGF‐β) and MMPs in renovascular hypertension …”
mentioning
confidence: 99%
“…The chronic cardiac hypertrophy model is used to simulate the chronic progression of heart remodeling in some chronic cardiovascular diseases such as hypertension. 18 The acute cardiac hypertrophy model reflects cardiac remodeling following acute cardiac injuries. 19 The safety of AuNPs in ISO-induced chronic cardiac hypertrophy model has been demonstrated in our previous study.…”
mentioning
confidence: 99%
“…Similarly, anti-fibrotic effect of metoprolol has been found in other studies. For example, metoprolol reduced myocyte hypertrophy and collagen deposition in a rat model of renovascular hypertension-induced cardiac hypertrophy [29]. Moreover, Serpi et al [30] suggested that metoprolol treatment attenuated adverse remodeling via decreased apoptosis and fibrosis in the peri-infarct region in a model of coronary ligation in rats.…”
Section: Discussionmentioning
confidence: 99%